Pengembangan Media Game dan Quiz Berbasis Web untuk Meningkatkan Motivasi Belajar Siswa dalam Pembelajaran PAI di SMP Negeri 21 Surabaya - Azril Wira Kusuma; Mashuri Muslim; Iksan (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
Today's generation can no longer be separated from gadgets. In order to overcome the addiction to gadgets, education should be arranged so that it can be accessed via gadgets so that students do not put aside learning on the grounds that gadgets are more interesting. With this background, the problem formulation prepared by the researcher is 1) What is the process of developing Game & Quiz media using web-based learning media in Islamic Religious Education subjects at SMP Negeri 21 Surabaya? 2) How effective is the Game & Quiz media using web-based learning media to increase students' learning motivation in Islamic Religious Education subjects at SMP Negeri 21 Surabaya? The type of research is development research using the ADDIE model. Data collected used observation, documentation and questionnaire data collection techniques. The data obtained is in the form of quantitative data. Respondents in this research were Islamic Religious Education subject teachers, class IX students, and product validators. The results of the research show that 1) the process of developing media games and quizzes goes through the analysis stage or analyzing data, problems and potential, the design stage or designing the product, the development stage or developing the product, the implementation stage or product trial, the evaluation stage or revising the trial product. 2) the use of game and quiz learning media in Islamic Religious Education learning in increasing student learning motivation at SMP Negeri 21 Surabaya has proven to be effective, this is shown by an increase in student learning motivation by 75% to 81% and the t test result is -2.21 which is shows that -2.21 is included in the Ha acceptance area.